0552 Evaluating the Use of a Titratable Pre-Fabricated Mandibular Advancement Device to Predict Response to a Custom Device. (27th April 2018) - Chang, J; Arguelles, J; Kim, J; Becker, K; Woodrum, R; Vega, D; Kim, J; Demerjian, G; Thompson, F; Bautista, M; Hwang, D
Abstract: Introduction: Predicting improvement in obstructive sleep apnea (OSA) with mandibular advancement device therapy (MAD) based on clinical and cephalometric data remains suboptimal. We explore the accuracy of a pre-fabricated MAD (PF) to predict response to MAD. Methods: We retrospectively reviewed OSA patients at the Kaiser Permanente sleep center (Fontana, CA) evaluated for MAD. Patients attended an education class where they were constructed a titratable PF (ApneaRx, Apnea Sciences Corporation). After a period of home-acclimation, patients were scheduled for sleep testing with PF and device was advanced until AHI4% significantly improved (≥50% improvement and <15) or PF determined to be ineffective. A custom MAD (SomnoDent, SomnoMed, Inc) was ordered in those with a significant response to PF and willing to use, and follow-up sleep testing was performed. Results: 239 patients enrolled into the class, and 181 completed sleep testing with a PF. 102 (56.4%) had a significant response to PF. 61 (59.8%) underwent construction of a custom MAD (custom)—(62.3% male, 52.4 ± 11.3 years, BMI 30.1 ± 4.4). Mean AHI4% decreased from baseline 18.4 ± 8.6 to PF 4.8 ± 3.1/custom 6.6 ± 5.2 (All p<0.01) with a mean improvement of 72.7%±13.3%/74.9%±14.2%. 73.8% of custom met definition for significant improvement. However, several patients with custom did not quite meet 50% AHI improvement while achieving AHI<15; these patients were clinically presumed "responders" and underwent further MAD advancement without requiring further testing. Inclusion of these patients (defined by custom AHI<15) resulted in 57 of 61 PF total responders to custom (PPV 93.4%). Patients that responded to MAD had lower BMI (30.4 ± 5.2 vs. 32.5 ± 5.7, p=0.01), AHI (17.3 ± 9.0 vs. 20.9 ± 14.8, p=0.06), T90% (6.6%±10.2% vs. 11.8%±16.9%, p=0.02), and minimum saturation (82.0%±5.3% vs. 79.4%±6.8%, p<0.01). Conclusion: Titratable pre-fabricated MAD based on real-world clinical experience demonstrated high value in predicting positive response to custom MAD, although negative predictive value could not be determined. This mechanism may potentially improve cost-effectiveness of MAD therapy. Support (If Any): N/A.